Appendices A. Quadratic Reciprocity Via Gauss Sums

Appendices A. Quadratic Reciprocity Via Gauss Sums

1 Appendices We collect some results that might be covered in a first course in algebraic number theory. A. Quadratic Reciprocity Via Gauss Sums A1. Introduction In this appendix, p is an odd prime unless otherwise specified. A quadratic equation 2 modulo p looks like ax + bx + c =0inFp. Multiplying by 4a, we have 2 2ax + b ≡ b2 − 4ac mod p Thus in studying quadratic equations mod p, it suffices to consider equations of the form x2 ≡ a mod p. If p|a we have the uninteresting equation x2 ≡ 0, hence x ≡ 0, mod p. Thus assume that p does not divide a. A2. Definition The Legendre symbol a χ(a)= p is given by 1ifa(p−1)/2 ≡ 1modp χ(a)= −1ifa(p−1)/2 ≡−1modp. If b = a(p−1)/2 then b2 = ap−1 ≡ 1modp,sob ≡±1modp and χ is well-defined. Thus χ(a) ≡ a(p−1)/2 mod p. A3. Theorem a The Legendre symbol ( p ) is 1 if and only if a is a quadratic residue (from now on abbre- viated QR) mod p. Proof.Ifa ≡ x2 mod p then a(p−1)/2 ≡ xp−1 ≡ 1modp. (Note that if p divides x then p divides a, a contradiction.) Conversely, suppose a(p−1)/2 ≡ 1modp.Ifg is a primitive root mod p, then a ≡ gr mod p for some r. Therefore a(p−1)/2 ≡ gr(p−1)/2 ≡ 1modp, so p − 1 divides r(p − 1)/2, hence r/2 is an integer. But then (gr/2)2 = gr ≡ a mod p, and a isaQRmodp. ♣ 2 A4. Theorem The mapping a → χ(a) is a homomorphism from Fp to {±1}. Proof. We compute ab a b ≡ (ab)(p−1)/2 = a(p−1)/2b(p−1)/2 ≡ p p p so χ(ab)=χ(a)χ(b). ♣ A5. Theorem If g is a primitive root mod p, then χ(g)=−1, so g is a quadratic nonresidue (from now on abbreviated QNR) mod p. Consequently, exactly half of the integers 1,2,...,p − 1 are QR’s and half are QNR’s. Proof.Ifh2 ≡ g mod p then h is a primitive root with twice the period of g, which is impossible. Thus by (A4), χ(ag)=−χ(a), so a → ag gives a bijection between QR’s and QNR’s. ♣ A6. The First Supplementary Law From the definition (A2) and the fact that (p − 1)/2isevenifp ≡ 1 mod 4 and odd if p ≡ 3 mod 4, we have −1 1ifp ≡ 1mod4 =(−1)(p−1)/2 = p −1ifp ≡ 3mod4. A7. Definition Let K be a field of characteristic = p such that K contains the p-th roots of unity. Let ζ ∈ K be a primitive p-th root of unity. Define the Gauss sum by p−1 a τ = ζa. p p a=1 A8. Theorem 2 − (p−1)/2 τp =( 1) p. Proof. From the definition of Gauss sum and (A4) we have p−1 ab τ 2 = ζa+b. p p a,b=1 3 For each a, we can sum over all c such that b ≡ ac mod p. (As c ranges over 1,... ,p− 1, ac also takes all values 1,... ,p− 1.) Thus p−1 p−1 a2c τ 2 = ζa+ac. p p a=1 c=1 a2 Since p = 1, this simplifies to p−1 p−1 c τ 2 = ζa(1+c) . p p c=1 a=1 If 1 + c ≡ 0modp then 1,ζ1+c,ζ2(1+c),... ,ζ(p−1)(1+c) runs through all the roots (zeros) of Xp − 1 (note that ζp = 1). But the coefficient of Xp−1 is 0, so the sum of the roots is 0. Therefore the sum of ζ1+c,ζ2(1+c),... ,ζ(p−1)(1+c) is -1. If 1 + c ≡ 0modp, then we are summing p − 1 ones. Consequently, p−2 c −1 τ 2 = − +(p − 1) . p p p c=1 ≡ ↔ − − −1 (Note that 1 + c 0modp c = p 1.) We can sum from 1 to p 1ifweadd p , hence p−1 c −1 τ 2 = − + p . p p p c=1 The sum is 0 by (A5), and the result follows from (A6). ♣ A9. The Law of Quadratic Reciprocity Let p and q be odd primes, with p = q. Then p q =(−1)(p−1)(q−1)/4. q p Thus if either p or q is congruent to 1 mod 4, then p is a QR mod q if and only if q is a QR mod p; and if both p and q are congruent to 3 mod 4, then p isaQRmodq if and only if q is a QNR mod p. Proof. Let K have characteristic q and contain the p-th roots of unity. For example, take p K to be the splitting field of X − 1 over Fq. Then q 2 (q−1)/2 τp =(τp ) τp which by (A8) is (q−1)/2 (p−1)/2 (−1) p τp. 4 Thus q − (p−1)(q−1)/4 (q−1)/2 τp =( 1) p τp. But by the binomial expansion applied to the definition of τp in (A7), p−1 a τ q = ζaq p p a=1 (Recall that K has characteristic q,soaq = a in K.) Let c ≡ aq mod p and note that q−1 q = p p 1 because the product of the two terms is ( p ) = 1. Thus p−1 c q q τ q = ζc = τ . p p p p p c=1 q We now have two expressions (not involving summations) for τp ,so q (−1)(p−1)(q−1)/4 p(q−1)/2 = . p (q−1)/2 p F Since p =(q ) by (A2), the above equation holds not only in K but in q, hence p can be written as a congruence mod q. Finally, multiply both sides by ( q ) to complete the proof. ♣ A10. The Second Supplementary Law 2 2 =(−1)(p −1)/8 p so 2 1ifp ≡±1mod8 = p −1ifp ≡±3mod8. Thus if p ≡ 1 or 7 mod 8, then 2 is a QR mod p, and if p ≡ 3or5mod8,then2isa QNR mod p. Proof. Let K be a field of characteristic p containing the 8th roots of unity, and let ζ be a primitive 8th root of unity. Define τ = ζ + ζ−1. Then τ 2 = ζ2 + ζ−2 +2. Now ζ2 and ζ−2 are distinct 4th roots of unity, not ±1, so they must be negatives of each other (analogous to i and −i in C). Therefore τ 2 = 2. Modulo p we have 2 2 τ p =(τ 2)(p−1)/2 τ =2(p−1)/2 τ = τ = (ζ + ζ−1). p p 5 But by definition of τ, τ p =(ζ + ζ−1)p = ζp + ζ−p. Now (again as in C) ζp + ζ−p and ζ + ζ−1 will coincide if p ≡±1 mod 8, and will be negatives of each other if p ≡±3mod 8. In other words, 2 ζp + ζ−p =(−1)(p −1)/8(ζ + ζ−1). Equating the two expressions for τ p, we get the desired result. We can justify the appeal to the complex plane by requiring that K satisfy the constraints ζ2 + ζ−2 = 0 and 2 ζp + ζ−p =(−1)(p −1)/8(ζ + ζ−1). ♣ A11. Example We determine whether 113 is a QR mod 127: 113 127 ≡ ( 127 )=(113 ) because 113 1mod4; 127 14 a ( 113 )=(113 ) because ( p ) depends only on the residue class of a mod p; 14 2 7 7 ≡ ( 113 )=(113 )( 113 )=(113 ) by (A4) and the fact that 113 1mod8; 7 113 ≡ ( 113 )=( 7 ) because 113 1mod4; 113 1 ≡ ( 7 )=(7 ) because 113 1mod7 1 and since ( 7 ) = 1 by inspection, 113 is a QR mod 127. Explicitly, 113 +13(127) = 1764 = 42 2. A12. The Jacobi Symbol Let Q be an odd positive integer with prime factorization Q = q1 ···qs. The Jacobi symbol is defined by s a a = . Q q i=1 i It follows directly from the definition that a a a a a aa = , = . Q Q QQ Q Q Q Also, a a a ≡ a mod Q ⇒ = Q Q because if a ≡ a mod Q then a ≡ a mod qi for all i =1,... ,s. Quadratic reciprocity and the two supplementary laws can be extended to the Jacobi symbol, if we are careful. 6 A13. Theorem If Q is an odd positive integer then −1 =(−1)(Q−1)/2. Q Proof. We compute − s − s 1 1 (q −1)/2 s (q −1)/2 = = (−1) j =(−1) j=1 j . Q q j=1 j j=1 Now if a and b are odd then ab − 1 a − 1 b − 1 (a − 1)(b − 1) − + = ≡ 0mod2, 2 2 2 2 hence a − 1 b − 1 ab − 1 + ≡ mod 2. 2 2 2 We can apply this result repeatedly (starting with a = q1,b = q2) to get the desired formula. ♣ A14. Theorem If Q is an odd positive integer, then 2 2 =(−1)(Q −1)/8. Q Proof. As in (A13), s s 2 2 (q2−1)/8 = = (−1) j . Q q j=1 j j=1 But if a and b are odd then a2b2 − 1 a2 − 1 b2 − 1 (a2 − 1)(b2 − 1) − + = ≡ 0mod8. 8 8 8 8 a2−1 (a−1)(a+1) 2 − ≡ In fact 8 = 8 is an integer and b 1 0 mod 8. (Just plug in b =1, 3, 5, 7.) Thus a2 − 1 b2 − 1 a2b2 − 1 + ≡ mod 8 8 8 8 and we can apply this repeatedly to get the desired result.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    12 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us